Globalisation of local banks - Chua, Piang Sze (2015)
The purpose of this project is to analyse the local banks' perceptions of globalisation, their current strategic positions and the feasibility of going global. The five representative banks chosen for their significant roles in Singapore's banking sector are, The Development Bank of Singapore, Oversea-Chinese Banking Corporation, United overseas Bank, Overseas Union Bank and Tat Lee Bank. In the process of doing so, a study of the expansion efforts of the banks and a comparison to that of a 'near global' bank- Hongkong and Shanghai Banking Corporation (HSBC) were made. This report is broadly divided into two sections, a theoretical and an empirical section. Sources of information for both sections were derived from newspaper clippings, international banking journals, bank management books, the banks' financial report, interviews and statistics from the relevant authorities. The theoretical section provided a framework for the report in that general discussions of the definition, factors, methods, strategies and problems of globalisation were presented as concerned all globalising organisations. This was followed by the empirical section where the focus was narrowed down to that of the five local banks and HSBC. It started with an analysis of the banks' background and past and present overseas expansionary efforts to arrive at their current strategic positions in the global market as compared to HSBC. Then based on the interviews conducted, the local banks' views on the points discussed in the theoretical section were presented. From the interviews, the main constraints to globalisation cited were lack of funds, human resource and natural customer base, regulations and restrictions and competition in the foreign markets. However other factors like saturation of the domestic market, robust growth of the regional economy and the need to serve their customers investing abroad have forced them to look into overseas market. Among the four methods of globalisation, setting up of representative offices, branches and joint-venture are the most popular among the five local banks. Furthermore, 'carving a market niche' and tapping a market based on 'cultural affinity' were the two common strategies adopted by them. The concluding part showed that the local banks are still rather domesticated in Singapore. Their plans presently are to regionalise and immediate interests are shown in the Asian Pacific region especially in the Asean countries. This led to a detailed study of the market opportunities presented by various Asia Pacific countries like India, Philippines, Taiwan, Thailand, Vietnam.